Managing the River Commons : Fishing and New England's Rural Economy - Reardon, Erik (Book collections on Project MUSE., 2021)
"New England once hosted large numbers of anadromous fish, which migrate between rivers and the sea. Salmon, shad, and alewives served a variety of functions within the region's preindustrial landscape, furnishing not only maritime areas but also agricultural communities with an important source of nutrition and a valued article of rural exchange. Historian Erik Reardon argues that to protect these fish, New England's farmer-fishermen pushed for conservation measures to limit commercial fishing and industrial uses of the river. Beginning in the colonial period and continuing to the mid-nineteenth century, they advocated for fishing regulations to promote sustainable returns, compelled local millers to open their dams during seasonal fish runs, and defeated corporate proposals to erect large-scale dams. As environmentalists work to restore rivers in New England and beyond in the present day, Managing the River Commons offers important lessons about historical conservation efforts that can help guide current campaigns to remove dams and allow anadromous fish to reclaim these waters"--